Problematika volného kování - Máčala, Daniel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Práce předkládá přehled o problematice volného kování. Je vytvořena na základě literární studie teoretického základu s doplněním obrázků k dané problematice. Pojednává obecně o volném kování, jeho principu a rozdělení. Dále jsou popsány nejčastější užívané výchozí polotovary, jejich ohřev a typy strojů. Hlavní důraz je kladen na základní kovářské operace, které jsou podrobně popsány. Pro lepší představu využití volného kování, jsou uvedeny příklady výkovků z výrobních firem.

The thesis submits the overview about issues of open die forging. It is written based on literary studies of theoretical basis with addition of pictures regarding the problematics. It generally deals with open die forging, its principles and sorting. Then the most frequently used initial semi-finished products, its heating and types of machines, are described. The main focus is put on basic forging operations which are concretely described. For the better image of usage of open die forging the examples of forging from manufacturing companies are introduce.
Issues of open die forging
Keywords: kování; volné kování; ingot; prodlužování; pěchování; forging; open die forging; ingot; fullering; upsetting